THE REPRESENTATION OF SUICIDAL BEHAVIOR IN A STAR IS BORN MOVIE: A FREUDIAN PSYCHOANALYSIS READING - Jihans Siska Arnetta; Dina Amelia (Linguistics and Literature Students' Journal, 2022)
This research uses a movie entitled A Star is Born that was released in 2018 as the object of analysis. The movie focuses on the story of a seasoned-musician, namely Jackson Maine, who had difficulties in quitting from drugs and alcohol. The movie ended on the scene of Jack who attempted suicide. Considering the story of the movie, this research aims to examine the portrayal of suicidal behavior in the movie as portrayed through the main character, Jack. In this research, the researcher used descriptive qualitative methods to describe and explain the issue of suicidal behavior in A Star is Born movie. Hence, the data are in the form of dialogues and scenes that were taken from the movie. To analyze the suicidal behavior of Jack through the scenes, the researcher used the theory of suicidal behavior as well as Freudian psychoanalysis. By conducting the analysis, this research found that Jack showed the acts that fulfilled the suicidal behavior according to the American Psychiatric Association (APA). The suicidal behavior of Jack was done due to Jack who often follows his Id, according to the Freudian Psychoanalysis.Keywords: Freudian psychoanalysis, suicide, suicidal behavior